Opportunities and Drawbacks of Implementing the Bologna Process in Kurdistan Higher Education Universities: A Regional Review - Zanyar Nathir Ghafar; Omar Mohammad-Ameen Ahmad Hazaymeh; Bareq Raad Raheem; Majid Wajdi; Ida Bagus Artha Adnyana; Anak Agung Raka Sitawati (International Journal of Pedagogy and Learning Community (IJPLC), 2025)
This review paper examines the adoption and implementation of the Bologna Process across higher education institutions in the Kurdistan Region of Iraq (KRI). Employing a secondary data review approach, the study synthesizes findings from institutional reports, policy documents, and empirical research conducted at universities in Sulaimani, Erbil, Duhok, Zakho, Halabja, Soran, Garmian, and Raparin. The analysis reveals several opportunities arising from the Bologna Process, including curriculum reform towards student-centered learning, the adoption of the European Credit Transfer and Accumulation System (ECTS), improved quality assurance mechanisms, and enhanced potential for international academic collaboration. Despite these advancements, the study identifies significant challenges such as inconsistent policy coordination, inadequate digital infrastructure, faculty resistance to pedagogical change, and limited institutional capacity in quality assurance. These issues hinder the full integration of Bologna principles across the region. Based on the findings, the paper proposes key recommendations: standardizing policy frameworks, investing in digital and administrative infrastructure, expanding faculty training programs, and strengthening institutional governance. These strategies aim to promote a more coherent and sustainable implementation of the Bologna Process, contributing to the ongoing modernization of higher education in the Kurdistan Region.